2020
DOI: 10.1002/ejhf.1744
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death after myocardial infarction

Abstract: This article refers to 'Predictors of sudden cardiac death in high-risk patients following a myocardial infarction' by K.F. Docherty et al., published in this issue on pages 848-855.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Induction of arrhythmias after myocardial infarction is associated with an increased risk of sudden death (Zaman and Kovoor, 2014;Chatterjee and Levy, 2020). Following MI, the risk for ventricular tachyarrhythmia and sudden cardiac death in patients is increased (Hegyi et al, 2018;Li et al, 2020;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of arrhythmias after myocardial infarction is associated with an increased risk of sudden death (Zaman and Kovoor, 2014;Chatterjee and Levy, 2020). Following MI, the risk for ventricular tachyarrhythmia and sudden cardiac death in patients is increased (Hegyi et al, 2018;Li et al, 2020;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We congratulate the authors for their thoughtful consideration of competing risk in this study, 3 and would highlight that given the co‐association of the SCD risk factors identified with non‐SCD mortality, we would not anticipate that those identified at highest risk of SCD in this study would necessarily be more likely to benefit from ICD therapy. As we have proposed previously, 18 for any given absolute risk of SCD, the proportional risk of SCD serves as a ‘rheostat’ for ICD survival benefit ( Figure ) 19,20 . Indeed, when assessed in prior randomized ICD trials, increasing absolute SCD rates were associated with attenuated survival benefit as these patients had an even greater absolute risk of non‐SCD mortality, thereby lowering their proportional risk of SCD ( Figure ) 16,17 .…”
Section: Figurementioning
confidence: 86%
“…MI is a crucial clinical challenge and explaining in detail its molecular events would help to highlight our strategies for reducing the death rate in patients with cardiovascular diseases ( Chatterjee & Levy, 2020 ; Pollard, 2000 ). Thus, exploring the molecular regulator of cardiomyocytes activity will introduce a new insight into MI treatment.…”
Section: Discussionmentioning
confidence: 99%